Web Service pada Sistem Curriculum Vitae (CV) Dosen Terintegrasi Berbasis Arsitektur REST API - Ulumi, Desepta Isna; Perwitasari, Anggi (Jurusan Informatika Universitas Tanjungpura, 2024)
Software called web services serves as a connector that allows various systems to communicate with each other without being affected by platform differences and without connecting directly to a database. Web services allow existing services on the old system to communicate with the new system without changing either. In this research, we will explain the development of a web service that can integrate several websites in the Untan Information System (Tanjungpura University), namely SIAKAD (Digital Media for Academic Guidance, Monitoring and Assessment Services), SPOTA (Final Project Outline Support System) and SIMLPPM (System Management Information for Research and Community Service Institutions) so that the data contained in the three information systems can match each other in real time. In addition, this research uses REST API (Representational State Transfer Application Programming Interface) technology for data exchange. System testing uses black box testing which tests twelve menu features and seven submenus showing that the features can run well as well as the User Acceptance Test (UAT) which shows results of 89.89%. Test results show that the system is well received by users. It is hoped that with this system lecturers will automatically have a CV that is updated every year, according to data that has been input into other systems owned by Untan, so that CV documents can be produced for research needs, community service and so on. fast, efficient and error free. input data.